Real-time control of ELM and sawtooth frequencies: similarities and differences. (2nd December 2015) - Lennholm, M.; Frigione, D.; Graves, J.P.; Beaumont, P.S.; Blackman, T.; Carvalho, I.S.; Chapman, I.; Dumont, R.; Felton, R.; Garzotti, L.; Goniche, M.; Goodyear, A.; et al.
Abstract: ELMs and Sawteeth, located in different parts of the plasma, are similar from a control engineering point of view. Both manifest themselves through quiescent periods interrupted by periodic collapses. For both, large collapses, following long quiescent periods, have detrimental effects while short periods are associated with decreased confinement. Following the installation of the all metal 'ITER like wall' on JET, sawteeth and ELMs also play an important role by expelling tungsten from the core and edge of the plasma respectively. Control of tungsten has therefore been added to divertor heat load reduction, NTM avoidance and helium ash removal as reasons for requiring ELM and sawtooth control. It is therefore of interest to implement control systems to maintain the sawtooth and ELM frequencies in the desired ranges. On JET, ELM frequency control uses radial field 'kicks' and pellet and gas injection as actuators, while sawtooth control uses ion cyclotron resonance heating (ICRH). JET experiments have, for the first time, established feedback control of the ELM frequency, via real time variation of the injected gas flow [001 ]. Using this controller in conjunction with pellet injection allows the ELM frequency to be kept as required despite variations in pellet ELM triggering efficiency. JET Sawtooth control experiments have, for the first time, demonstrated that low field side ICRH, as foreseen for ITER, can shorten sawteeth lengthened by central fast ions [002 ]. The development of ELM and sawtooth control could be key to achieve stable high performance JET discharges with minimal tungsten content. Integrating such schemes into an overall control strategy will be required in future tokamaks and gaining experience on current tokamaks is essential.